Development and Validation of Tofacitinib Citrate in API and Tablet Formulation by UV Spectroscopic and HPTLC Method - Ikhar, Rina; Sabale, Prafulla; Somkuwar, Komal; Sawale, Vaibhav; Sabale, Vidya; Warokar, Amol (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction: In the present study, quantification of tofacitinib citrate by UV spectroscopy and HPTLC method were done and validated as per ICH guidelines. Tofacitinib was approved in 2012, it was first JAK inhibitor for the treatment of moderate to severe rheumatoid arthritis. In the UV spectroscopic method tofacitinib citrate was quantified at 287 nm using methanol as a diluent. In HPTLC method, toluene: methanol: acetic acid (7.5:2:0.5% v/v/v) were used as a mobile phase and an HPTLC silica gel 60 F254 precoated plate was used as stationary phase. Materials and Methods: Double beam UV spectrophotometer UV-1800 shimadzu along with a pair of quartz cells 10 mm and for HPTLC camag TLC scanner 4 with linomat 5 equipped with visionCATS (version 3.2.23095.1) were used. API of tofacitinib citrate was procured from Hetero Healthcare, Hyderabad. Methanol was used as diluent. Results: Tofacitinib citrate was quantified by densitometric as absorbance mode at 287 nm and the chromatogram was obtained at the Rf value of 0.428±0.051. The linearity was assessed using UV and HPTLC methods at the concentration range of 1-5 µg/mL and 100-500 ng/spot respectively; with correlation coefficient (r2) 0.9993 and 0.9906 respectively. The percent recoveries for UV and HPTLC method were calculated as 100.41-100.72% and 99.86-101.3% respectively. The limit of detection and limit of quantitation for UV method was found to be 0.1649 µg/mL and 0.4998 µg/mL respectively and for HPTLC method 58.66 ng/spot and 177.76 ng/spot respectively. The percent purity of tofacitinib citrate was found to be 98.66-101.60% 100.22% for UV and 98.03-100.74% 99.42% for HPTLC method. Conclusion: The accuracy, percent recovery and percent purity calculated from both the methods were best compared to other available methods. HPTLC method is more sensitive as its detection limit very less than UV method.
Keywords: UV spectroscopy; HPTLC method; Tofacitinib citrate; Tablet formulation